2017
DOI: 10.1111/1440-1681.12811
|View full text |Cite
|
Sign up to set email alerts
|

Adipose‐derived mesenchymal stem cells therapy for acute kidney injury induced by ischemia‐reperfusion in a rat model

Abstract: Acute kidney injury (AKI) represents a group of complicated syndromes with a high mortality rate. The administration of adipose-derived mesenchymal stem cells (ADMSCs) has been tested as a possible treatment method for AKI. The long-term evaluation of AKI induced by ischemia/reperfusion (IR) and the probable renal protection of ADMSCs are limited. In this study we have established a rat AKI model induced by IR and investigated the possible protective effects of ADMSCs. Adult Sprague-Dawley (SD) rats were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 42 publications
1
23
0
1
Order By: Relevance
“…In recent years, stem cell therapy has drawn much attention for the treatment of AKI [ 7 ]. As a main player, MSCs derived from different sources like adipose, bone-marrow and human umbilical cord have shown renoprotective effects in several models of toxin or IRI-induced AKI [ 31 33 ]. Meanwhile, numerous controversies have arisen regarding safety, cost, availability, and ethical considerations of MSCs [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, stem cell therapy has drawn much attention for the treatment of AKI [ 7 ]. As a main player, MSCs derived from different sources like adipose, bone-marrow and human umbilical cord have shown renoprotective effects in several models of toxin or IRI-induced AKI [ 31 33 ]. Meanwhile, numerous controversies have arisen regarding safety, cost, availability, and ethical considerations of MSCs [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the efficacy and possible benefits from stem cells application in the management of ischemic injuries, the state of acute ischemia has been provoked in experimental animal models. It was observed that the administration of ASCs could protect tissues against the consequences of acute ischemic injury and modulate their reorganization after myocardial infarction, ischemic stroke, or acute renal ischemic injury [82][83][84][85][86][87][88][89]. Nevertheless, it is worth mentioning that the results of a randomized clinical trial did not support the thesis that the injection of ASCs could minimize kidney injury and could improve renal function after the induced acute ischemia [90].…”
Section: Animal Modelsmentioning
confidence: 99%
“…Another very important pathophysiological mechanism involved in AKI I/R is the so-called sterile inflammation. In this regard, ASC have shown to downregulate the expression of inflammatory cytokines and chemokines (IL-6, TNF-α, IL-1β, IFN⋎, CXCL2) and upregulate the anti-inflammatory cytokine IL-10 ( 233 , 234 ). Macrophage number and migration was reduced in a study using iPSC and hWJ-MSC-EVs where the effect was observed in terms of downregulation of MCP-1 and CX3CL1 (chemoattractant factor for macrophages) ( 160 , 235 ).…”
Section: Msc Therapy In the Treatment Of Kidney Diseases: State Of Thmentioning
confidence: 99%